Gambaran Hasil Pemeriksaan Kadar Elektrolit Klorida (Ci) Pada Penderita Hipertensi - Jurnal Syarif (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2016)
This study aims to determine the levels of electrolytes chloride (CI) in patients with hypertension. This type of research is observational laboratory with descriptive approach is to determine the examination results electrolyte levels of chloride (CI) in hypertensive patients with a master's touch screen using a photometer Cyanat Thio method. Thio Cyanat method is a method of examination where the intensity of color formed in accordance with chloride concentrations determined photometer so that the results can be relied upon. Rated normal chloride levels in units of mEq/L for adults is 95-105 mEq / L while normal values chioride levels in units of mmol /L is 97-111 mmol/ L. Based on research conducted at the Laboratory D-IlI Health Analyst University of Indonesia Eastern Tterhadap 5 sample of hypertensive adults, the results obtained by the A 108 mmol/ L, B. 94 mmol /L, C: 87 mmol / L, D: 86 mmol /L, E: 93 mmol /L, the percentage of chloride electrolyte levels (CF) which is normal as much as 1 sample (20%), and electrolyte levels of chloride (CI) below normal by 4 samples (80%)